Stranded steel wire ropes Part 4. Specification for ropes for lifts - British Standards Institution (London BSI, 1987)
Ropes, Wire ropes, Steel-wire ropes, Strands, Cores (ropes), Diameter, Breaking load, Design, Tensile strength, Weight (mass), Rope pitch, Circular shape, Triangular shape, Materials handling, Grades (quality), Materials handling components
Cross References BS 462, BS 463, BS 464, BS 2763, BS 5281, BS 5655:Part 1, BS 5750:Part 2, BS 6570, ISO 2408, EN 81-1
International Relationships ISO 4344:1983 Not Equivalent
Replaces BS 329:1968
Replaced By BS EN 12385-5:2002
Superseded, Withdrawn
Keywords: Steel-Wire Ropes -- Standards